Study of Fuzzy Controller to control vertical position of an air-cushion tracked vehicle - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (2011)
This paper presents the fuzzy logic control system of an air-cushion tracked vehicle (ACTV) operating on swamp peat terrain. Vehicle vertical position is maintained by using an inflated air-cushion system attached with the vehicle. It is desired that the vehicle vertical position be maintained at a desired position so that vehicle obtains sufficient traction control and to propel the driving system. To accomplish this task, it is required that the error between the actual position and the desired position equal to zero, and the differential position rate also be equal to zero. Therefore, the main purpose of this study is to develop an appropriate control strategy for an air-cushion system by using fuzzy logic expert system. Air-cushion system is controlled by the electronic proportional control valve and fuzzy logic controller (FLC) with associating the output signal of the distance (height) measuring sensor attached with the vehicle. In this control scheme the fundamental goal is to employ the fuzzy logic expert system to set the fuzzy rules and to actuate the electronic proportional valve in order to obtain appropriate valve control actions. Experimental values are taken in the laboratory for control system testing to investigate the relationship between vehicle vertical position and air-cushion system.